Quantitative characterisation of impaction events during femoral broaching in total hip arthroplasty. (February 2020) - Preutenborbeck, Martin; Reuter, Julian; Ferrari, Elisabetta
Highlights: Off-axis design of broach handle resulted in reduction of load transmission. The strike location affected the occurrence of transverse forces. Suboptimal broach progression was reached at low mallet velocities/forces. Abstract: Total hip arthroplasty (THA) broaching involves impacting a broach handle with a mallet, facilitating force transmission to progress broaches into the femoral medullary canal. Limited surgical access during direct anterior THAs increases off-axis forces, potentially contributing to tissue damage. The aim was to characterise impactions during broaching. In a cadaver lab, movement of handle, femur and instrumented mallet was tracked during direct-anterior approach (DAA) and posterior approach (PA). Mallet velocity, broach displacement and input energy were calculated. Following the cadaver lab, different impaction strategies were investigated using bone simulants for a simulated DAA. The effects of reduced mallet velocity inputs and the influence of different impaction locations on the broach handle strike plate were investigated. To seat the broach in cadaveric bone, lower impaction energy (−59%) and number of strikes (−53%) were observed during PA compared to DAA. Suboptimal broach progression was reached in bone simulant at low mallet velocities (3.1 ± 0.3 m/s). Impacting the strike plate's upper part caused larger deflections ( p  < 0.001) of the Sawbones femur which suggested that higher off axis forces occurred. Awareness of reduced load transmission during DAA broaching using off-axis broach handles, compared to the traditional PA, could help promoting a more efficient and careful impaction strategy in surgeries.